Regulatory element map of sheep reproductive tissues: functional annotation of tissue-specific strong active enhancers - Meng, Zhu; Chu, Mingxing; Yang, Hao; Zhang, Shiwen; Wang, Qiangjun; Chen, Jiahong; Ren, Chunhuan; Pan, Zhangyuan; Zhang, Zijun (Frontiers in Veterinary Science, 2025)
IntroductionComprehensive functional annotation of the genome is crucial for elucidating the molecular mechanisms underlying complex traits and diseases. Although functional annotation has been partially completed in sheep, a systematic annotation focused on reproductive tissues remains absent.MethodsIn this study, we integrated 60 transcriptomic and epigenomic datasets from five reproductive tissues. Using a multi-omics approach, we predicted 15 distinct chromatin states and conducted thorough functional annotation.ResultsWe established the first regulatory element atlas for sheep reproductive tissues and examined the roles of these elements in reproductive traits and disease. In total, we annotated 1,680,172 regulatory elements, including 83,980 tissue-specific strong active enhancers (EnhAs).DiscussionEnhancers were identified as critical drivers of tissue-specific functions, operating through sequence-specific transcription factor binding and direct regulation of target genes. Key transcription factors associated with reproductive function included INHBA (ovary), KITLG (oviduct), Snai2 (cervix), WNT7A (uterine horn), FOLR1 (uterine body), and SALL1 (shared uterine regions). Additionally, our findings support the potential of sheep as a promising model for investigating embryonic development and miscarriage. This work lays a theoretical foundation for future research into the molecular mechanisms of complex traits and diseases in sheep.